2008
DOI: 10.1152/ajpheart.01264.2007
|View full text |Cite
|
Sign up to set email alerts
|

Eucapnic intermittent hypoxia augments endothelin-1 vasoconstriction in rats: role of PKCδ

Abstract: We reported previously that simulating sleep apnea by exposing rats to eucapnic intermittent hypoxia (E-IH) causes endothelin-dependent hypertension and increases constrictor sensitivity to endothelin-1 (ET-1). In addition, augmented ET-1-induced constriction in small mesenteric arteries (sMA) is mediated by increased Ca(2+) sensitization independent of Rho-associated kinase. We hypothesized that exposing rats to E-IH augments ET-1-mediated vasoconstriction by increasing protein kinase C (PKC)-dependent Ca(2+)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 43 publications
6
32
1
1
Order By: Relevance
“…In agreement with previous findings using endotheliumdisrupted mesenteric arteries (Allahdadi et al, 2008b), this study demonstrates that augmented ET-1-mediated vasoconstriction is dependent on PKCd in endothelium-intact mesenteric arteries. This PKCd-dependent mechanism does not appear to be present in all vascular beds since isolated aortic segments from sham-and IH-exposed rats both show attenuated vasoconstriction in response to pan-PKC and cPKC inhibitors but PKCd inhibition has no effect (Allahdadi et al, 2008b).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with previous findings using endotheliumdisrupted mesenteric arteries (Allahdadi et al, 2008b), this study demonstrates that augmented ET-1-mediated vasoconstriction is dependent on PKCd in endothelium-intact mesenteric arteries. This PKCd-dependent mechanism does not appear to be present in all vascular beds since isolated aortic segments from sham-and IH-exposed rats both show attenuated vasoconstriction in response to pan-PKC and cPKC inhibitors but PKCd inhibition has no effect (Allahdadi et al, 2008b).…”
Section: Discussionsupporting
confidence: 93%
“…This PKCd-dependent mechanism does not appear to be present in all vascular beds since isolated aortic segments from sham-and IH-exposed rats both show attenuated vasoconstriction in response to pan-PKC and cPKC inhibitors but PKCd inhibition has no effect (Allahdadi et al, 2008b). Furthermore, inhibition of PDK-1, a kinase activator of PKCd, with OSU-03012 attenuates ET-1-mediated vasoconstriction in arteries from IH-but not from sham-exposed rats.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Both are supported by our previous observations that these arteries have a modest increase in the protein levels of the ET A receptor and that postreceptor signal transduction is altered by E-IH exposure (4,5). Indeed, ET A receptors appear to activate PKC␦ in arteries from E-IH-exposed rats but not in sham arteries, further indicating that E-IH alters the signaling cascade of this receptor in vascular smooth muscle (3). Recent studies in diabetic rats also found that despite elevated levels of ET-1, vascular sensitivity to ET-1 was increased in small but not large arteries (53).…”
Section: ) Et B Receptor Mrna Expression Is Not Different In Tissuessupporting
confidence: 78%
“…PKC activation not only mediates ET-1-induced vascular contraction (2,16,123) and regulates ET-1 receptors expression (112), but is intimately linked to ET-1-mediated regulation of hypertrophy, growth, proliferation, and survival in vascular smooth muscle cells (12). PKC activation (PKC-␦), via phosphorylation of STAT3, also mediates ET-1-induced decreases in arterial eNOS protein levels and NO generation (150) as well as ET-1-induced vascular formation of superoxide anion (103).…”
Section: Signaling Pathways Activated By Et-1 That Can Be Modified Bymentioning
confidence: 99%